THE EFFECT OF HSP65 MYCOBACTERIUM TUBERCULOSIS ON THE VACCINATION TOWARDS AORTIC THICKNESS OF MICE THAT HAVE BEEN INDUCED ATHEROSCLEROSIS - Sari, Dian Amelia (Malang Neurology Journal, 2017)
Background. Atherosclerosis is an inflammatory process of the blood vessels accompanied by immune activity which is signed by the enhancement of histopathologic. One of the protective proteins in the human artery wall expressed when there is endothelial stress is HSP60. HSP65 is an HSP60 homologous protein found in bacteria, such as Mycobacterium tuberculosis.Objective. To determine the effect of HSP65 through aorta thickness of mice.Methods. This research applied experimental study using post-test control group design in which subjects were divided into 5 groups. Each group consisted of 5 mice. Group I mice fed a diet normokolesterolemia (negative control), group II mice given atherogenic diet without vaccine (positive control), group III mice given atherogenic diet and 0,5μg accination, group IV mice were given atherogenic diet and 0,75μg vaccination, group V mice were given atherogenic diet and 1μg vaccination.Results. There was a difference between the atherogenic diet and vaccination group (p <0.05). There was a significant decrease in aortic thickness of atherosclerosis mice with HSP65 vaccination dose 0,75µg (r= -0,449, p= 0,024).Conclusion. HSP65 Mycobacterium tuberculosis vaccination can reduce the thickness of the aorta in mice induced atherosclerosis and the effective dose is 0.75 mg dose.